The Influence of Social Media Promotion and Price on Purchase Decisions at Reyhani Store - Mauliandini Mufidah; Syaeful Bakhri (Faculty of Islamic Economics and Business IAIN Syekh Nurjati Cirebon, 2023)
Poor quality social media promotions and inconsistent product prices contribute to consumers' lack of interest in making purchasing decisions for a product. The purpose of this study is to ascertain the impact of social media promotion and price on purchasing decisions. This study is a quantitative research method which uses purposive sampling with a population of resellers at the Reyhani Store, Tengah Tani Branch. The type of data used in this study is primary data by using questionnaire to collect data, and the scale used for measurement is a 1-5 Likert scale. Multiple linear regression is used in this research data analysis technique. The test results found that social media promotion and price has a positive and significant influence on purchasing decisions. According to the findings of this study, Reyhani shop owners should be able to maintain fixed and stable product prices while also improving the quality of online marketing on various social media platforms.